France China Archives
France China Archives est une plateforme en libre accès qui inventorie les archives photographiques de la Chine conservées en France. Elle prend en compte les fonds privés et publics dont le contenu couvre la période allant des années 1840 à nos jours. Cette plateforme a été pensée pour fournir un espace numérique savant à l’étude de la variété des pratiques photographiques en Chine, tout en rendant les ressources en français accessibles à la communauté scientifique, aux étudiants et au grand public.
Keywords: _open access

Chinese Women's Studies Database glossary | Cheng Yu Tung East Asian Library
The Chinese Women’s Studies database is a unique resource for information about women’s social conditions, women’s movements and the rise of feminism in China. It is built upon a collection of card records donated to Cheng Yu Tung East Asian Library in the early 1980s by Dr. Bobby Siu, who was then a PhD student of Carleton University, Ottawa, Ontario. He collected the information and put it down on thousands of cards while he was conducting research on Chinese women. The records were all handwritten in either English or Chinese. Topics covered range from education and marriage to women's movement as well as revolutions and wars.
Keywords: _open access

Funü zazhi 婦女雜誌 (1915-31)
Funü zazhi is one of the most long-lived women’s magazines in China. It was published by Shanghai Commercial Press between1915-31.
Keywords: _open access

Modern Women's Journal Database 近代婦女期刊資料庫
Includes 214 titles, about 110,000 records of Women's magazines. Developed and maintained by the Institute of Modern History Institute, Academia Sinica. Free but need registration.
Keywords: _open access

抗日战争与近代中日关系文献数据平台
An open access data platform, developed by the Institute of of the Modern History at the Chinese Academy of Social Sciences, which provides free access to data (books, newspapers, archival documents, journals, images, audios, and videos) related to Sino-Japanese relations from 1731.
Keywords: _open access

Chinese Womens Magazine
An open access database of a research project that examines four influential women's magazines published in Shanghai between 1904-1937. Provides research materials including the images of the original issues of the magazines
Keywords: _open access

Chinese collections at the Bodleian Libraries - Bodleian Libraries (2024)
Chinese books have been part of the Bodleian Libraries’ collections since the Library’s foundation in 1602. The first known acquisition of a Chinese book dates to 1604. Our founder – Sir Thomas Bodley – was instrumental in starting this collection, even though he did not speak or understand Chinese.  His handwriting appears in the 1604 book. The collection grew over the following four centuries and it continues to grow today. It is now one of the most significant Chinese rare book and manuscript collections outside China, containing the largest number of Chinese books that arrived in Europe in 17th century. As part of a ten-year project funded by Chung Hon Dak Foundation, we have digitised over 1,800 items, as well as worked with the local Chinese community to explore our collections in more detail.
Keywords: _open access

Collections numériques de l’Institut Français de Pondichéry - Inist (2024)
Keywords: _open access

Chinese_Archaeological_Journals
Chinese Archaeology Journals Index database contains 20.000 entries from Kaogu and Wenwu. (click "Se connecter en tant qu'invité")
Keywords: _open access